Use of Local Resources from Oil Palm Bunch Ash combined with Cow Manure to Grow and Produce Sweet Corn (Zea mays saccharata Sturt) Planted in Peat Soil to Support Smart Agriculture - Warsito; Oktaria, Oktaria Duwi Pratiwi; Budianta, Dedik; Ayu, Ieke Wulan (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2023)
Sweet corn is a food crop that has a sweeter taste than ordinary corn. It has high economic value and has a shorter harvest time. The demand for corn is increasing in Indonesia but corn production is not sufficient to meet it. For this reason, efforts to increase sweet corn production are needed to consume the people. The purpose of this study was to determine the effect of oil palm bunch ash and cow manure ameliorants on the growth and production of sweet corn (Zea mays saccharata Sturt) on peat soil. The pot experiment was conducted in Bandar Agung Village, Lalan District, Musi Banyuasin, South Sumatra of Indonesia dated from December 2022 to March 2023. This study used a Randomized Factorial Block Design which consisted of 2 factors which were the first factor was dose of oil palm bunch ash consisting of control, oil palm bunch ash at 20 tons ha-1 and 60 tons ha-1. The second factor was dose of cow manure at control, 42 tons ha-1 and 84 tons ha-1. Total treatment was 9 combinations and it were repeated 3 times. For each treatment was left 2 plant samples. The results showed that no significant effect for plant height, number of leaves, plant fresh weight and plant dry weight. Application of 60 tons ha-1 of oil palm bunch ash + 42 tons ha-1 of cow manure showed the best combination results on sweet corn growth because it has the highest found on each variable observed. Keywords: Ameliorant, cow manure, oil palm bunch ash, peat, sweet corn